Macroeconomic Uncertainty, Ceos’ Corporate Distress Experience And Corporate Cash Holdings - Khong, Jiunn Shyan (2024)
The recent outbreak of the COVID-19 pandemic and the Ukraine war have spurred a growing concern about the impact of macroeconomic uncertainty on corporate activities, particularly corporate cash holdings as cash represents the most valuable asset of a firm given its functions and liquidity. Using a sample of listed firms in the United States from 1992 to 2021, the finding of this study supports the tradeoff theory, the real-option effect, and the risk-averse effects, which suggest that firms hoard more cash in response to macroeconomic uncertainty. Besides, drawing from the upper echelons literature, which reveals that decisions made by CEOs are largely influenced by their past experiences, this study also investigates whether corporate distress experiences of CEOs matter to cash holdings decisions of firms when dealing with macroeconomic uncertainty. It is found that CEOs with corporate distress experience has a significant interaction effect on the macroeconomic uncertainty-corporate cash holdings relationship. Furthermore, this study further discovers that the impact of macroeconomic uncertainty on corporate cash holdings is greater in firms which managed by CEOs with recent or multiple corporate distress experience. This findings in line with the recency law, the reinforcement hypothesis, and the saliency hypothesis which claim that recent or multiple experience has a more robust impact than distant or single experience on an individual’s decision making. Overall, this study provides novel insights into the underlying effect of macroeconomic uncertainty on corporate cash holdings, the channel that reinforce this effect through the lens of CEOs’ personal trait, and whether the variation in the CEOs’ personal trait matters.